2007
DOI: 10.1021/ct600312f
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Calibration of Transition-Metal Elements for the Spin-Polarized Self-Consistent-Charge Density-Functional Tight-Binding (DFTB) Method:  Sc, Ti, Fe, Co, and Ni

Abstract: Citation for the original published paper (version of record):Zheng, G., Witek, H A., Bobadova-Parvanova, P., Irle, S., Musaev, D G. et al. (2007) Parameter calibration of transition-metal elements for the spin-polarized self-consistent-charge density-functional tight-binding (DFTB) method: Sc, Ti, Fe, Co, and Ni. Journal of Chemical Theory and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(244 citation statements)
references
References 70 publications
(135 reference statements)
10
227
0
Order By: Relevance
“…Instead, we employed self-consistent charge density functional tight binding (SCC-DFTB) calculations to calculate potential energies and forces for the catalytic system, using standard parameterizations. [73][74][75] We note that previous BHMC simulations have confirmed that this computational approach is capable of describing the main intermediates in the catalytic cycle to be studied here. 52 The calculation details for the description of the catalytic hydroformylation process were generally the same as described above; minor changes to the atomic pair cuto↵ distances in Table I were introduced such that optimised molecular structures at the DFTB level gave the correct corresponding molecular graphs in our simulations, and values for the new parameters associated with cobalt were derived in a similar manner.…”
Section: B Catalytic Hydroformylation Of Ethenesupporting
confidence: 71%
“…Instead, we employed self-consistent charge density functional tight binding (SCC-DFTB) calculations to calculate potential energies and forces for the catalytic system, using standard parameterizations. [73][74][75] We note that previous BHMC simulations have confirmed that this computational approach is capable of describing the main intermediates in the catalytic cycle to be studied here. 52 The calculation details for the description of the catalytic hydroformylation process were generally the same as described above; minor changes to the atomic pair cuto↵ distances in Table I were introduced such that optimised molecular structures at the DFTB level gave the correct corresponding molecular graphs in our simulations, and values for the new parameters associated with cobalt were derived in a similar manner.…”
Section: B Catalytic Hydroformylation Of Ethenesupporting
confidence: 71%
“…The DFTB method is À approximately two orders of magnitude faster than first principles DFT and therefore enables longer simulations and provides more adequate model systems for nonequilibrium dynamics of nanosized clusters with quantum mechanical treatment of electrons. In addition, metal-carbon parameters for DFTB have recently been developed by the Morokuma group [57]. A Ànite electronic temperature À approach [58,59] ensures the applicability of the DFTB/MD method for nanometer size metal particles with high electronic densities of states around the Fermi level, as it allows the occupancy of each molecular orbital to change smoothly from 2 to 0 depending on its orbital energy.…”
Section: Dftb-based MD Simulationsmentioning
confidence: 99%
“…Recent work in the development of SCC-DFTB has focused on the pragmatic advancement of the model, and has resulted in new, efficient, and ever-improving methods, 4,[12][13][14] parameters, 9,[15][16][17][18] and computer codes. 2,19,20 The approach we have chosen is quite different, in that we start from an ab initio-like model that reproduces DFT results very well without the use of parameters, and then identify where and quantify by how much the model breaks down when various approximations are introduced.…”
Section: Introductionmentioning
confidence: 99%